Vitamin A deficiency affects gene expression in the Drosophila melanogaster head - Deepshe Dewett; Maryam Labaf; Khanh Lam-Kamath; Kourosh Zarringhalam; Jens Rister (G3: Genes, Genomes, Genetics, 2021)
AbstractInsufficient dietary intake of vitamin A causes various human diseases. For instance, chronic vitamin A deprivation causes blindness, slow growth, impaired immunity, and an increased risk of mortality in children. In contrast to these diverse effects of vitamin A deficiency (VAD) in mammals, chronic VAD in flies neither causes obvious developmental defects nor lethality. As in mammals, VAD in flies severely affects the visual system: it impairs the synthesis of the retinal chromophore, disrupts the formation of the visual pigments (Rhodopsins), and damages the photoreceptors. However, the molecular mechanisms that respond to VAD remain poorly understood. To identify genes and signaling pathways that are affected by VAD, we performed RNA-sequencing and differential gene expression analysis in Drosophila melanogasterarrestin